The effect of exercise model and limb length on the accuracy of kuda service in sepak takraw - Hakim Irwandi Marpaung; Suryansah suryansah; Abdul Hakim Siregar (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This study aims: (1) the differences in the effect of static and dynamic targets on the accuracy of kuda service; (2) the effect long and short limb on the accuracy of kuda service; and (3) the interaction between of static, dynamic targets and limb lengths (long and short) on the accuracy of kuda service by sepak takraw male players. This study method was an experimental research factorial design. The population was 32 athletes from PSTI Club Sleman and Bantul. 24 samples were chosen based on Slovin formula using the simple random sampling method. Data were collected through pretest and posttest by measurement leg length and service accuracy ability tast. Analyzed using analysis of variance (two-way AN0VA) at the significant level of α = 0.05. Results showed that: (1) there was a significant difference in effect of static dynamic targets on accuracy of kuda service; (2) there was significant differenceein effect long short limbs on accuracy of kuda service; (3) there was a significant interaction between of static, dynamic targets and limb length (long and short) to the accuracy of kuda service in sepak takraw male players.